The Roses of Jay DeFeo and Bruce Conner: Belated Thoughts on Intermediality and Friendship - Susan Felleman (Interfaces)
Bruce Conner’s 1967 short film, The White Rose, is an artifact of a particular place and time—Fillmore Street, San Francisco, one day in 1965—and a document of Conner’s friendship with the artist Jay DeFeo, painter of The Rose, the monumental painting at its center, which she labored over for eight years, and which had to be removed by a team of professionals when she was forced to give up her apartment and studio. Intermediality is a central property of Bruce Conner’s oeuvre, reflecting the background as visual artist he brought to filmmaking, beginning with A Movie in 1958. The poignant film he made years later of his friend and her work may be his most narrative but it is also profoundly intermedial, capturing with a handheld camera as gestural as a paint stroke, in a few minutes, the irrevocable spaces, textures, activities, and losses of the day The Rose left home.